Energy performance optimization for Army installations. (February 2013) - Zhivov, Alexander; Liesen, Richard J; Richter, Stephan; Jank, Reinhard; Underwood, David M; Neth, Dieter; Woody, Alfred; Björk, Curt
Buildings contribute to a large fraction of energy usage worldwide. In the United States alone, buildings consume about 40% of total energy expenditure, including 71% of electricity and 54% of natural gas. 1 The Army alone spends more than US $1 billion for building-related energy expenses. The 2005 Energy Policy Act 2 requires that Federal facilities be built to achieve at least a 30% energy savings over the 2004 International Energy Code or ASHRAE Standard 90.1-2004, as appropriate, and that energy efficient designs must be life-cycle cost effective. According to the Energy Independence and Security Act (EISA 2007), 3 new buildings and buildings undergoing major renovations shall be designed to reduce consumption of energy generated off-site or on-site using fossil fuels, as compared with such energy consumption by a similar building in fiscal year 2003 (FY03) as measured by Commercial Buildings Energy Consumption Survey (CBECS) or Residential Energy Consumption Survey (RECS) data from the Energy Information Agency, by 55% in 2010, 80% by 2020, and 100% by 2030. Current US research efforts focus on renewable energy sources and single-building energy efficiency, and pay little attention to integration and minimization of energy use in building communities, i.e. Army installations and university campuses. There is no over arching 'power delivery/energy storage/demand' architecture and methodology to accomplish this. This article describes the Net Zero fossil fuel-based energy optimization process and illustrates it with an example based on the results of study conducted for a cluster of buildings at Fort Irwin, CA. Application of the energy optimization process to new construction and major retrofit project shows17–20 that use of high performance building envelope (improved insulation and air tightness), advanced lighting strategies, and efficient HVAC systems results in significant energy savings (site and source) in Army buildings in all climates. When buildings built or retrofitted with a high performance building envelope, using advanced lighting systems and highly efficient 'low exergy' HVAC systems, reach a theoretical energy use minimum, the largest percentage of the remaining energy use in the building will be related to its 'mission': lighting, plug loads, and domestic hot water usage. Additional savings may be achieved with measures related to improved efficiency of power generation supplied to the building (co- and tri-generation) and use of energy supplied from renewable energy sources. The integrated energy solution recommended here demonstrates that vastly improved energy efficiency and GHG reduction are feasible in the context of a normal scale development using proven approaches from the USA and elsewhere. Moreover, the optimization process can be applied to new construction and major renovation of buildings and building clusters projects developed for low energy communities.